2009
DOI: 10.1038/aps.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin inhibits prostate cancer invasion, motility and migration by suppressing vimentin and MMP-2 expression

Abstract: Aim: Silibinin is known to exert growth inhibition and cell death together with cell cycle arrest and apoptosis in human prostate cancer cells. Whether silibinin could inhibit the invasion, motility and migration of prostate cancer cells remains largely unknown. This study was designed to evaluate this efficacy and possible mechanisms using a novel highly bone metastatic ARCaP M cell model. Methods: Four prostate cancer cell lines, LNCaP, PC-3, DU145, and ARCaP M , were used in this study. These cells were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 23 publications
2
68
0
Order By: Relevance
“…The switch from cytokeratin to vimentin expression takes place at the periphery and the invasive front of the tumor (Wu et al, 2009). As in tumor growth, hypoxia induces HIF-1, as a pleiotropic master switch of the cell biological processes responsible for tumor invasion.…”
Section: Breaking Barriers: Cancer Invasion Metastasis and Cell Metamentioning
confidence: 99%
“…The switch from cytokeratin to vimentin expression takes place at the periphery and the invasive front of the tumor (Wu et al, 2009). As in tumor growth, hypoxia induces HIF-1, as a pleiotropic master switch of the cell biological processes responsible for tumor invasion.…”
Section: Breaking Barriers: Cancer Invasion Metastasis and Cell Metamentioning
confidence: 99%
“…Silibinin was obtained from Sigma (St. Louis, MO, USA) and dissolved in dimethyl sulfoxide (DMSO). For silibinin treatment, stock solution (0.05 M in DMSO) was added into culture medium to achieve appropriate concentration (100 μmol/l) as described (26), and then incubated with cells for indicated time periods (24-72 h), whereas DMSO solution without silibinin was used as control. Cell morphology was examined under a light microscope and photomicrographs were taken using Olympus C5050Z digital camera (x200, magnification).…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing the unique highly bone metastatic ARCaP M cell model with a spindle-shaped mesenchymal phenotype, we have previously demonstrated that silibinin could inhibit the invasion, motility and migration of prostate cancer cells in vitro (26). The ARCaP M cells are derived from ARCaP E cells which undergo EMT by exposing to soluble factors such as TGF-ß1 plus EGF, IGF-1, ß2-microglobulin or a bone microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [13] . Human BCa cell lines and HDF-a cells were washed with cold PBS twice; then, total cellular protein lysates were prepared with RIPA buffer [50 mmol/L Tris (pH 8.0), 150 mmol/L NaCl, 0.1% SDS, 1% NP40 and 0.5% sodium deoxycholate] containing proteinase inhibitors (1% protease inhibitor cocktail and 1 mmol/L phenylmethanesulfonyl fluoride, both from Sigma, St Louis, MO, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%